A Prussian blue anode for high performance electrochemical deionization promoted by the faradaic mechanism. Issue 35 (31st August 2017) - Guo, Lu; Mo, Runwei; Shi, Wenhui; Huang, Yinxi; Leong, Zhi Yi; Ding, Meng; Chen, Fuming; Yang, Hui Ying
Abstract : Electrochemical deionization as a sustainable process for efficient seawater desalination. Abstract : Desalination is a sustainable process that removes sodium and chloride ions from seawater. Herein, we demonstrate a faradaic mechanism to promote the capacity of capacitive deionization in highly concentrated salt water via an electrochemical deionization device. In this system, ion removal is achieved by the faradaic mechanism via a constant current operation mode, which is improved based on the constant voltage operation mode used in the conventional CDI operation. Benefiting from the high capacity and excellent rate performance of Prussian blue as an active electrochemical reaction material, the designed unit has revealed a superior removal capacity with an ultrafast ion removal rate. A high removal capacity of 101.7 mg g −1 has been obtained with proper flow rate and current density. To further improve the performance of the EDI, a reduced graphene oxide with nanopores and Prussian blue composite has been synthesized. The PB@NPG has demonstrated a high salt removal capacity of 120.0 mg g −1 at 1 C with an energy consumption of 6.76 kT per ion removed, which is much lower than most CDI methods. A particularly high rate performance of 0.5430 mg g −1 s −1 has been achieved at 40 C. The faradaic mechanism promoted EDI has provided a new insight into the design and selection of host materials for highly concentrated salt water desalination.